Entrenamiento en rodillo y resistencia a la velocidad en ciclistas de ruta - Medina Núñez, Diego Paul (2026)
The present research study, entitled “Roller Training and Speed Endurance in Road Cyclists,” aimed to determine the influence of roller training on speed endurance in pre-junior road cyclists from the Espinosa Bike Club. An incremental test performed on a smart roller was used as the evaluation method, recording blood lactate levels, heart rate, and relative power output (W) under pre-test and post-test conditions. The methodology followed a quasi-experimental approach, analyzing the characteristics of roller training and its influence on speed endurance in road cyclists, with the purpose of optimizing athletes’ physical preparation. Likewise, the research design was descriptive and propositional, allowing for a detailed identification of the factors influencing the development of speed endurance by analyzing the real characteristics of roller training and its physiological impact on cyclists. Data were processed using SPSS statistical software, applying normality tests as well as parametric and nonparametric tests for related samples. The study found positive physiological adaptations following the roller training program, primarily reflected in metabolic responses and mechanical performance